The effects of 17b-estradiol in cancer are mediated by estrogen receptor signaling at the plasma membrane - Acconcia, Filippo; Marino, Maria (Frontiers in Physiology, 2011)
Two different isoforms of the estrogen receptors (i.e., ERα and ERβ) mediate pleiotropic 17β-estradiol (E2)-induced cellular effects. The ERs are principally localized in the nucleus where they act by globally modifying the expression of the E2-target genes. The premise that E2 effects are exclusively mediated through the nuclear localized ERs has been rendered obsolete by research over the last 15 years demonstrating that ERα and ERβ proteins are also localized at the plasma membranes and in other extra-nuclear organelles. The E2 modulation of cancer cell proliferation represents a good example of the impact of membrane-initiated signals on E2 effects. In fact, E2 via ERα elicits rapid signals driving cancer cells to proliferation (e.g., in breast cancer cells), while E2-induced ERβ rapid signaling inhibits proliferation (e.g., in colon cancer cells). In this review we provide with an overview of the complex system of E2-induced signal transduction pathways, their impact on E2-induced cancer cell proliferation, and the participation of E2-induced membrane-initiated signals in tumor environment.